2020
DOI: 10.1038/s41746-020-00332-0
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for voice assistants to support healthcare delivery during a health crisis and pandemic

Abstract: To prevent the spread of COVID-19 and to continue responding to healthcare needs, hospitals are rapidly adopting telehealth and other digital health tools to deliver care remotely. Intelligent conversational agents and virtual assistants, such as chatbots and voice assistants, have been utilized to augment health service capacity to screen symptoms, deliver healthcare information, and reduce exposure. In this commentary, we examined the state of voice assistants (e.g., Google Assistant, Apple Siri, Amazon Alex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 26 publications
1
86
0
1
Order By: Relevance
“…Last, public health organizations should partner with technology companies to encourage the delivery of medical care through VAs [ 33 ]. In the recent COVID-19 pandemic, the Centers for Disease Control and Prevention used Microsoft’s Healthcare Bot service (text-based) to deliver a relevant and up-to-date information and self-assessment mechanism to the public [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last, public health organizations should partner with technology companies to encourage the delivery of medical care through VAs [ 33 ]. In the recent COVID-19 pandemic, the Centers for Disease Control and Prevention used Microsoft’s Healthcare Bot service (text-based) to deliver a relevant and up-to-date information and self-assessment mechanism to the public [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging technology for monitoring and overall strengthening of the infodemic response should be considered in LMIC contexts. 11 Establishing systematic monitoring, disease surveillance and evaluation system as well as promoting scientific research using robust methodologies and tools can inform existing infodemic or design responsive interventions and generate evidence for policymaking. Promotion of collective learning through the formation of communities of practice for regular sharing of experiences, knowledge and best practices is called for.…”
Section: A Multipronged Approachmentioning
confidence: 99%
“…Every technological device that could be used is a valuable asset in preventing the contamination with the virus. This is why VAs could be used with healthcare communication, like asking standard exam questions, triaging, screening, receiving questions for providers, and offering basic medication guidelines [ 53 ]. Such implementations would decrease dependency on providers for routine tasks, but also reduce the impact of delayed care.…”
Section: Previous Workmentioning
confidence: 99%
“…Ref. [ 53 ] concluded that different VAs showed disconnection with public health authorities, while the information presented by the VAs is many times not up-to-date and not reliable. This is why there is a need to improve the features of VAs, but also the coordination between the stakeholders in terms of requirements and necessities.…”
Section: Previous Workmentioning
confidence: 99%